DEVELOPMENT OF LIFE SKILLS EDUCATION AS CHARACTER BUILDING - Defitrika, Fajar; Mahmudah, Fitri Nur (International Journal of Educational Management and Innovation, 2021)
The industrial era 4.0 requires that every individual must have superior competence and wise morals. Life skill education is an effective strategy to face the XXI century competition. However, there has been no development in line with the demands, resulting in much unemployment in Indonesia. Character education is encouraged to maintain and strengthen the culture and character of the nation. However, in reality, character education has not yet integrated into all school-based development programs. This research explores the development of character education based on life skill education at Pondok Pesantren Modern Muhammadiyah Boarding School (PPM MBS) Yogyakarta. This qualitative research uses an ethnographic approach.Â  Researchers' data is through the interview, observation, and documentation techniquesâ€”data analysis process with data reduction stages, data presentation, and conclusion. Triangulation sources and techniques used as a test of data validity. This study's findings show the strengthening of character education through life skills education orienting on self-development and boarding schools' cultural development. This study's findings recommend various life skill education programs that can develop and character education strategies in formal schools.